Policy Strategy for Increasing The Capacity of Human Resources Leaders of The DPRD Members of Bandung Regency - Kurniasih, Dewi (Journal of Research in Social Science and Humanities, 2022)
The ability of a leader and member of the DPRD, in the industrial era 4.0 is required to have the capacity of human resources in accordance with the era. Making a policy strategy for the capacity of human resource development in the council is a very important thing needed by the regional government and the central government. The DPRD Secretariat needs to become a professional plenary staff in line with the strengthening of the role and position of DPRD in the regional government system. The discussion is related to the presence of PP No. 41 of 2007 concerning Regional Government Organizations. Government Regulation No. 41 of 2007 concerning the Secretariat of the DPRD, Article 4 states that the secretariat of the DPRD is an important factor in empowering the DPRD, where it plays a role in assisting and facilitating DPRD members in carrying out their duties and functions. In line with the development of the nation's constitutional and political life, including developments in people's consultative institutions, people's representative institutions, and regional representative institutions, and regional people's representative institutions, it is regulated in Law Number 27 of 2009 concerning the Structure and Position of the People's Consultative Assembly, the People's Representative Council. Regional Representative Council, Regional People's Representative Council, which is intended as an effort to restructure the composition and position of the People's Consultative Assembly, People's Representative Council, Regional Representative Council, and Regional People's Representative Council in the context of realizing people's deliberation institutions, people's representative institutions, and representative institutions. regions, as well as regional people's representative institutions.